Architecture Design of Electronic Manifest Document and ITS Challenges in Indonesia (Research, Society and Development, 2020)
Traditional shipping often experiences some accidents. Most of the ship operators did not complete the ship documents and did not create the documents for safety requirement, one of them is manifest. The absence of manifest makes the harbourmaster difficult to carry out the inspections. This research has objective to discuss on architecture design of the electronic system for manifest document. Also, to know the challenges of it in nature of traditional shipping in Indonesia. The research uses case study of traditional shipping in the Province of East Java by interviewing the respondents. The result showed that ITS development helps the safety improvement even though it still needs adjustment on the existing organization and conditions, but the resistance level of ITS implementation could be minimized. In conclusion, architecture design which developed as the basic ITS can help the harbourmaster to get easy access to manifest document. Thus it will increase the safety of the ships.